(untitled) (Annals of Medical Research, 2021)
Aim: Computed tomography (CT) and magnetic resonance imaging (MRI) are diagnostic modalities in pulmonary hydatid disease. We aimed to present CT and MRI findings in pulmonary hydatid disease. Material and Methods: CT and MRI findings of pulmonary hydatid cysts from January 2011 through June 2018 were evaluated retrospectively. CT images of 112 patients and MRI images of 27 patients were evaluated. Patients’ gender and ages, lesion number and distribution, concomitant organ involvement, complications, HU density of lesions on CT and signal characteristics of lesions on MRI were analyzed. T2 hypointense rim, T1 and T2 signal intensity, daughter vesicle and detached membranes were the evaluated parameters on MRI.Results: 147 hydatid cyst lesions of 119 (66 female, 53 male) patients with a mean age of 39.4±19.6 years were included in the study 62 (52.1%) of patients had isolated lung involvement. 79 of 119 patients (66.4%) had solitary lung lesion. Mean CT density of cysts were 16 HU. 25 of 32 cysts showed T2 hypointense rim on MRI. Conclusion: Imaging plays important role in diagnosis and presurgical evaluation of pulmonary hydatid disease. CT is mostly used in diagnosis; MRI should be a choice particularly in pediatric population.Keywords: Computed tomography; pulmonary; hydatid cyst; magnetic resonance.